Health optimizing physical education for senior high school - Cagurin, Giovanni B.; Tabimina, Iris Mirafuentes
"This textbook offers experiential learning for learners to adopt an active life for fitness and lifelong health. This book focuses on recreational activities that are associated with outdoor, natural or semi-natural settings and enables the learners to move safely and competently in these settings."
Includes references.
English text.
Keywords: Outdoor recreation; Physical education